2010
DOI: 10.4137/pri.s3693
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Genomic Studies on Lizard Venoms in the Last Decade

Abstract: Abstract:Traditionally man has looked to nature to provide cures for diseases. This approach still exists today in the form of 'bio-prospecting' for therapeutically-active compounds in venoms. For example, the venoms of many reptiles offer a spectacular laboratory of bioactive molecules, including peptides and proteins. In the last 10-15 years, there have been a number of major proteomic and genomic research breakthroughs on lizard venoms. In this current review, the key findings from these proteomic and genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In the recent review article by Kwok et al, 6 the concept of lizard (Lacerta) venoms as a potential source of biologically active therapeutic agents is critically surveyed. The review article discusses advances that have been made over the last several years in the development of minimally invasive procedures for harvesting lizard venoms.…”
Section: Why Lacerta?mentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent review article by Kwok et al, 6 the concept of lizard (Lacerta) venoms as a potential source of biologically active therapeutic agents is critically surveyed. The review article discusses advances that have been made over the last several years in the development of minimally invasive procedures for harvesting lizard venoms.…”
Section: Why Lacerta?mentioning
confidence: 99%
“…The helodermatid lizards are considered one of the most important species of lizards that have attracted increasing attention because of the broad utility of their venoms for biomedical applications. 6 Kwok et al describe how the venoms collected from the helodermatid lizards have permitted discovery of novel bioactive agents such as the exendin peptide toxin (sold over the counter as Byetta TM ) for the treatment of diabetes. 6,11 Remarkably, Kwok et al discovered a novel bradykinin-receptor inhibitory peptide from the venom of helodermatid lizards which was named helokinestatin.…”
Section: Why Lacerta?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to coagulotoxic, myotoxic and cytotoxic traits, Heloderma bites are often reported to cause pain, paresthesia, tachycardia and paralysis consistent with neurotoxic/cardiotoxic envenomation [ 23 , 25 , 26 ]. Previous research on Heloderma venom has revealed a myriad of protein families often recruited as neurotoxins [ 24 , 27 , 28 , 29 , 30 ]. However, few toxins have been isolated and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The toxins likely responsible for coagulotoxic activities in varanid lizards are kallikrein enzymes, which destructively cleave fibrinogen, and phospholipase A 2 (PLA 2 ), which block platelet aggregation, with both toxin types being homologous to Heloderma toxins with the same activity, reflective of their shared molecular evolutionary history and arising from the same venom glands [ 37 , 38 , 40 , 50 , 51 ]. However, many toxin families often recruited as neurotoxins in other organisms, such as AVIT, PLA 2 , cysteine rich secretory proteins (CRiSPs) and kunitz peptides, have been identified in the venom gland transcriptomes or venom proteomes of varanid and helodermatid lizards [ 15 , 24 , 27 , 28 , 29 , 30 , 37 , 40 ]. Indeed, the neurotoxic peptides in the AVIT and cholecystoxin classes were likely responsible for the strong contraction of rat smooth muscle after incubation with V. varius venom [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%